Event-related potentials in an associative word pair learning paradigm. (August 2021) - Farshad, Maryam; Pavlov, Yuri G.; Kotchoubey, Boris
Abstract: The study investigated the effect of unintentional learning of semantically unrelated word pairs on event-related brain potentials. Two experiments were conducted, in whose acquisition phase participants listened to five pairs of semantically unrelated words, each pair being repeated twenty times. In the test phase of Experiment 1, these "old" pairs were presented mixed with "new" pairs containing other words. In the test phase of Experiment 2, a third condition was added in which the first word in a pair was one of the words presented during acquisition but the second word was new. In both experiments, the second word in new word pairs elicited an N400 and a late (550–1000 ms) frontal positivity. The amplitude of the N400 to new second words in Experiment 2 was significantly larger when the first word in the pair was an old (previously learnt) word, as compared with the condition in which both first and second words were new. The results indicate that, in addition to a repetition effect, unintentional learning of word pairs results in building new associations between previously unrelated words. Highlights: Pairs of semantically unrelated words were presented. Repetition of the pairs created association between the words in a pair. Building associations involves both automatic and controlled processes. Frontal late positive complex reflects repetition effect only for second words.